Green Synthesis of Dehydrozingerone (DHZ) Utilizing Ionic Liquid Medium and Microwave Irradiation - Pertiwi, Annisa Mustika; Wahyuningrum, Deana (EduChemia: Jurnal Kimia dan Pendidikan, 2024)
Dehydrozingerone (DHZ), 4-(4-hydroxy-3-methoxyphenyl)-3-buten-2-one, a natural compound found in the rhizome of ginger plants (Zingiber officinale), exhibits a wide range of bioactivities, including antioxidant, anticancer, antimalarial, antidepressant, antifungal, and many other bioactivities. Conventionally, DHZ is synthesized through a cross-aldol Claisen-Schmidt condensation of vanillin and acetone, but this process often requires extended reaction times (up to 48 hours), results in low yields, and involves the excess use of organic solvents for purification. To address these limitations, this study aims to develop a green synthesis method for DHZ utilizing a 1-decyl-3-methylimidazolium bromide ([DMIM]Br) ionic liquid medium and microwave-assisted organic synthesis (MAOS) method. The experimental procedure involved optimizing the reaction conditions and varying the concentration of [DMIM]Br under microwave irradiation. Product characterization was performed by melting point determination, thin-layer chromatography (TLC), Fourier transform infrared (FTIR), and nuclear magnetic resonance (NMR) 1H (500 MHz, CDCl3) and 13C (125 MHz, CDCl3) spectroscopy. These findings indicate that the use of the [DMIM]Br ionic liquid significantly improved the purity and yield of DHZ products. The optimal conditions were synthesis from vanillin and acetone in a 1:10 molar ratio, 2.5 M NaOH, and 5% [DMIM]Br (w/v) using MAOS for 120 minutes (50°C, 300 W) to produce a 62.96% yield product in the form of a bright yellow solid with a melting point range of 129–130°C. The use of ionic liquids and MAOS provides a more efficient and environmentally friendly method for synthesizing DHZ, offering a significant reduction in reaction time and eliminating excess organic solvents, thus making it a promising alternative to traditional synthesis methods.